A new method for analyzing glistenings in hydrophobic acrylic intraocular lenses - M. Canberk Göktepe; Timur M. Yildirim; Grzegorz Łabuz; Thibaut Devogelaere; Gerd U. Auffarth; Ramin Khoramnia (Scientific Reports)
Abstract A reproducible, examiner-independent, objective method was introduced that uses swept-source optical coherence tomography (SS-OCT) and compared with established methods. Glistenings were induced in-vitro in twenty-five IOLs, five different IOL models: AcrySof SN60WF, AcrySof MA60AC, Clareon CNA0T0, PY60AD and Vivinex XY1. We calculated the glistening density within each IOL using light microscopy and SS-OCT. Glare effects were quantified with a straylight meter device (Oculus C-Quant). Image-processing software provided an objective tool for glistening quantification. Correlation parameters were evaluated between results of the three methods by using linear regression analysis. The PY60AD showed the highest amount of glistenings, followed by the MA60AC and SN60WF, whereas the CNA0T0 and XY1 showed the lowest values. There was a moderate correlation (R2 = 0.80) between the light microscopy and the straylight method. The analysis also showed a moderate correlation (R2 = 0.77) between the SS-OCT and the straylight method. At the same time, we found a strong and proportional relationship (R2 = 0.91) between the in-vitro reference method light microscopy and the SS-OCT method. We propose that SS-OCT can analyze glistenings precisely and allow objective estimation of the straylight induced by the glistenings within an IOL, permitting the clinician to measure pseudophakic patients’ glare symptoms.